Peran Layanan Digital dan Kemudahan Penggunaan dalam Membangun Keunggulan Bersaing Aplikasi Transportasi Online: Studi pada Pengguna Gojek - Desilia Eka Widyasari; Erista Febriani; Patrick Vandreno Chandra; Indah Noviyanti (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The goal of this research is to examine how user-friendliness and digital services impact the competitive advantage of the Gojek online transportation app. The ability of a business to offer outstanding digital services and accessibility for its customers is a major factor in its competitive edge in the age of the Industrial Revolution 4. 0. The data from the 100 Gojek users who responded to this study were analyzed using quantitative methods employing SmartPLS 4 software.The findings of the research demonstrate that competitive advantage is significantly and positively impacted by the two independent variables, digital services, and ease of use. According to the Rsquare value of 0. 644, these two variables can account for 64. 4% of the variance in competitive advantage. The validity, reliability, and structural model testing all demonstrate that the model developed in this study has satisfied the requirements for sufficient analysis.This study contributes theoretically and practically to our understanding of how important digital services and user-friendly interfaces are to improving the competitiveness of online transportation applications.The goal of this research is to examine how user-friendliness and digital services impact the competitive advantage of the Gojek online transportation app. The ability of a business to offer outstanding digital services and accessibility for its customers is a major factor in its competitive edge in the age of the Industrial Revolution 4. 0. The data from the 100 Gojek users who responded to this study were analyzed using quantitative methods employing SmartPLS 4 software.The findings of the research demonstrate that competitive advantage is significantly and positively impacted by the two independent variables, digital services, and ease of use. According to the Rsquare value of 0. 644, these two variables can account for 64. 4% of the variance in competitive advantage. The validity, reliability, and structural model testing all demonstrate that the model developed in this study has satisfied the requirements for sufficient analysis.This study contributes theoretically and practically to our understanding of how important digital services and user-friendly interfaces are to improving the competitiveness of online transportation applications. These findings are expected to be strategic input for Gojek and similar companies in developing service innovations that are oriented towards user experience.